Cocoa Production as Affected by Shade Tree Species and Soil Quality - Tria Yulianti; Soetanto Abdoellah; Didik Suprayogo; Niken Puspita Sari (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Cocoa is one of the agricultural commodities that have important role and are reliable in realizing agricultural development program of Indonesia. The cocoaproduction of Indonesia tends to decrease that caused by in appropriate farming. This research aimed to evaluate the shade management to cocoa productivity and evaluating the correlation between soil quality and the cocoa production with the different shade management. This research was conducted from October 2016 until June 2017 in Kaliwining Experimental Station and Soil Laboratory of Indonesian Coffee and Cocoa Research Institute (ICCRI), Jember, Indonesia. Clones at the trial plots were Sulawesi 1 and Sulawesi 2, 10 years old, and arranged in 3 m x 3 m spacing. The design of this research was conducted by observing parameters of sample trees on cocoa field. This research used three observation plots, with shade trees of leucaena (Leucaena sp.), teak (Tectona grandis), and teak combined with krete (Cassia surithensis) shade. The results indicated that shade species affected the cocoa production. Teak shade gave higher production of cocoa (i.e 3,01 kg.tree-1) compared to other species of shade (1.83 and 1.39 kg.tree-1 for leucaena and teak and krete combination, respectively). The correlation of soil quality with cocoa production showed that soil calcium content, earthworm biomass and soil bulk density were positively correlated with the production of cocoa. Shade species greatly affected the production in combination with the soil quality.